Cultivating scientific literacy and environmental management towards a sustainable urban poor community - Sharminii Devi Supramaniam,; Azlan Abas,; Rozida Mohd Khalid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The application of science is the main aspect of the scientific literacy culture. However, the application of science within the urban poor community is not holistically practiced. The study investigates the relationship between scientific literacy and environmental management that focuses on sustainable community b40. It also seeks a significant connection between the level of interest, exposure on science, awareness towards environmental management and the practices to preserve it. This study has analyzed previous studies to explore the way to cultivate the scientific literacy and environmental management towards a sustainable urban poor community. With the world facing critical environmental problems, an interdisciplinary approach to teaching science and environmental issues may help the people to regulate their learning, foster curiosity, and stimulate their motivation to learn, all of which would influence their overall knowledge on science and environment as well. The B40 Community holds the majority number in The Income Classifications of Malaysia so it is vital to educate this community on this issue. The urban poor community has an awareness of the culture of scientific literacy and environmental management, but the practices of managing it in daily life is at a low stage. To ensure that the goals of sustainable development are achieved, the application of science is vital to be practiced by the community, especially the urban poor.